Cognitive and emotional effects of occupational stress in nursing professionals - Paschoalini, Bruna [UNESP]; Oliveira, Mônica Martins [UNESP]; Frigério, Michele Cândida [UNESP]; Dias, Ana Luiza Ribeiro Pereira [UNESP]; Santos, Flávia Heloísa Dos [UNESP] (Escola Paulista de Enfermagem, Universidade Federal de São Paulo, 2008)
OBJECTIVE: Investigating the indicators of stress, anxiety, depression and the cognitive changes in members of the nursing team at Santa Casa de Misericórdia de Assis SP. METHODS: 66 nursing professionals participated in the study, evaluated by psychological and cognitive tracking instruments. RESULTS: The stress experience was not homogenous in the nursing team; high scores in the depression tracking were associated to low cognitive scores. CONCLUSION: Nursing auxiliaries and technicians were affected by stress. Therefore, worker's healthcare should be provided for the whole nursing team.

OBJETIVOS: Investigar, de forma integrada, posibles indicadores de alteraciones cognitivas, depresión, ansiedad y agentes estresores ocupacionales en auxiliares y técnicos de enfermería así como de enfermeros de diversos sectores de la Santa Casa de Misericordia de Asís-SP, por medio de instrumentos de rastreo psicológico y cognitivo. MÉTODOS: Participaron en el estudio 66 profesionales de enfermería, evaluados por instrumentos de rastreo psicológico y cognitivo. RESULTADOS: La experiencia de estrés no fue homogénea en el equipo de enfermería; los escores altos en el rastreo de depresión fueron asociados a escores cognitivos bajos. CONCLUSIÓN: Los auxiliares y técnicos de enfermería y enfermeros se vieron afectados por el estrés por lo que la atención a la salud del trabajador, debe ser ofrecida a todo el equipo de enfermería.
Efectos cognitivos y emocionales del estrés ocupacional en profesionales de enfermería
Keywords: Burnout, professional; Nursing, team; Anxiety; Depression; Neurobehavioral manifestations